A National Health Service : Report of the Council of the B.M.A. to the Representative Body (1944)
1944 1944 1940s 11 pages 5 Minister's behalf with the medical profession (see paragraph 52), have no powers of requiring practitioners to seek permission before entering new public practice, or of requiring young practitioners to enter any particular form of public practice, or any other similar powers. Local Administration 42. No satisfactory form of local administration is likely to be achieved unless and until a radical re-examination and reorganization of local government in this country has taken place. As, according to the White Paper, this review of local authority organization is not now contemplated, any local machinery decided upon for the administration of the health services should be regarded as provisional. 43. The establishment of joint health authorities, covering areas conterminous with existing major local authority boundaries and composed solely of the nominees of constituent major authorities, would tend to worsen rather than to improve the position in many respects. It would lead to an even greater division of local responsibility rather than to its concentration. Despite the provision for local advisory bodies (the Local Health Services Councils), the joint health authorities, with the composition proposed, would not be sufficiently informed or advised on the problems before them. 44. To some extent these disadvantages would be removed by including in the membership of joint health authorities, and in that of any committees set up by them, an adequate representation of the medical profession and associated professions and groups and of the voluntary hospitals, and by devising areas not necessarily conterminous with existing local authority areas but appropriate for hospital and medical purposes. 45. Nevertheless, there would still remain substantial disadvantages. The voluntary hospitals could not achieve real partnership by a minority representation on the body owning the local authority hospitals. The division of local health responsibility could be remedied only by concentrating all health functions in joint health authorities. There would still remain for many members of the public health service a severe contraction of interest and responsibility, so as to involve not only loss of status for the doctors but the future discouragement of able practitioners from entering this branch of medical work. 46. For these reasons the Association urges a different form of local organization. Pending the reform of areas and functions of existing local government authorities, there should be compulsorily established by legislation, in place of the Joint Board structure proposed in the White Paper, Regional Councils for national hospital and medical areas, not necessarily or usually conterminous with local authority boundaries. These Councils should be representative of local authorities, the medical profession and other vocational interests, and voluntary hospitals, the representatives to be appointed by the groups or bodies concerned. The function of these Regional Councils should be to advise the Minister on the planning of all hospital and health services in the region and on the disposition of centrally provided moneys. This planning should culminate in a scheme or schemes approved by the Minister for execution within the area covered by the Council. 47. Local authorities should continue, for the present, to own their institutions and to administer their health services, but should be required to conform to the general plan prepared by the Regional Council and approved by the Minister. Similarly, the voluntary hospitals would conform to the general plan, receiving their moneys either wholly from the Minister on the advice of the Regional Council, or partly from the Minister and partly from local authorities in accordance with the plan laid down by the Minister. 48. In relation to each County and County Borough Council there should be established by statute a Medical Advisory Committee, elected by the local profession and with functions and powers analogous to those of the Central Health Services Council. There should be effective liaison between the Medical Advisory Committee and the Central Health Services Council. Each County and County Borough Council should be statutorily required to consult such Medical Advisory Committees and to co-opt to their public health hospitals and similar committees representatives of the Medical Advisory Committee. Voluntary Hospitals 49. The local administrative plan expounded above would go some way towards securing real partnership between local authorities and voluntary hospitals. The financial arrangements would need consideration. However arranged, it should be possible for voluntary hospitals to receive as contracting parties a proper payment even up to the full cost incurred by them without losing their identity or status. The financial arrangements should secure that it is reasonably practicable for these hospitals, with such help as may be available to them from voluntary sources, to maintain their existing services and to embark upon necessary extensions. General Medical Practice 50. The terms and conditions of service, including remuneration, of general practitioners should be negotiated centrally between the Minister and representatives of the medical profession. These terms and conditions should guarantee, inter alia, the professional freedom of doctors and freedom of choice as between doctor and patient. They should provide for a method of remunerating doctors which relates the remuneration to the work done or the responsibility accepted. This method should obtain both in separate and in group practice. 51. The terms and conditions of service, including remuneration, for practitioners working in Health Centres, should these be established, should be similar to those affecting other general practitioners, save only for differences related to the different expenses involved. 52. The agreements of general practitioners — the content of which should be centrally negotiated — should be entered into between the practitioner and a body or bodies set up by the Minister expressly for the purpose. Such body or bodies should include ample representation of the profession, and should not consist wholly or substantially of local authority representatives. The proposed Central Medical Board, but without the proposed powers of compulsion, would be appropriate for this purpose, acting either directly or through local committees of the Central Medical Board, analogous to the existing Insurance Committees. General practitioners are unwilling to enter into contractual relationship with local authorities. Health Centres 53. The establishment of Health Centres as a national policy should be preceded by a period of scientific trial and experiment. Such experimentation should be organized on a scientific basis under the aegis of the Central Health Services Council, should take place in contrasting areas, and should be conducted over a period of three to five years. It should be undertaken in consultation with the local medical profession, and should include clinical, administrative, and financial experiments. The ultimate decision with regard to the policy of establishing Health Centres, including the types, should await the result and report of such experiments. Compensation 54. The acceptance of the proposals for scientific experiment before Health Centres become an established part of general medical practice has repercussions on the issue of compensation. It is clear to the Association, and strongly supported by the expert advice it has received, that the adoption of the proposal in the White Paper to compensate for loss of capital value of their practices those practitioners who enter Health Centre practice, would of itself affect adversely the capital value of all general practices. Such a step would have two effects. It 36/H24/42